Chemical Compositions of Essential Oils of Different Parts and Extract of Achillea santolina L. from Iran - Motavalizadehkakhky, Alireza; Ebrahimi, Zohreh; Emamiyan, Reyhane; Mohamadian, Atefeh; Abedi, Fatemeh (Asian Journal of Chemistry, 2013)
GC and GC-MS analysis of the isolated essential oils obtained by steam distillation from the flowers, leaves and stem of Achillea santolina L., known to have medicinal activity, collected from Iran. The constituents obtained by hexane-ether extraction of the aerial parts of Achillea santolina L. resulted in the identification of 48-59 constituents (96.1-98.0 % of the total oils and extract). Different parts of A. santolina were the valuable organs for the essential oil production representing a yield of 0.15-0.7 % (w/w). In the hydrodistilled oil of three parts and the extract of A. santolina, 1,8-cineole (3-5 %), camphor (3.8-5.1 %), terpinene-4-ol (4.0-7.1 %), fragranol (7.1-9.1 %), fragranyl acetate (20-37 %), a-terpinyl acetate (0.6-5.1 %), caryophyllene oxide (1.2-3.2 %), a-muurolol (1.1-3.6 %) and some alkanes, alkanoic acids and esters were principle components, also monoterpenes (7.1-9.1 %) and oxygenated monoterpenes (55.1-77.2 %) were dominant components.